Tropical infections as occupational diseases - labor inspectorate physicians' aspects of a complex problem - Paul J. Jansing; Audry Morrison; Travis W. Heggie; Thomas Küpper (University of Applied Sciences in Tarnow, Poland, 2021)
Background: Occupational physicians work directly with individual employees regarding diseases that has been caused or exacerbated by workplace factors. However, employees are increasingly required to travel for their work, including to tropical countries where they risk exposure to diseases they would not normally encounter at home (i.e., malaria). Such disease/s may also take days to months to incubate before becoming symptomatic, even after their return home, thus delaying and complicating the diagnosis. Proving this was an occupational disease with respective sick leave entitlement or compensation can be challenging. There is a lack of data concerning occupational diseases caused by tropical infections. Material and methods: Employee case records for the period 2003-2008 from the State Institute for Occupational Health and Safety of North-Rhine Westphalia in Germany were analysed and assessed within Germany's regulatory framework. These records included Germany's largest industrial zone. Results: From 2003-2008the suspected cases of "tropical diseases and typhus", categorized as occupational disease "Bk 3104" in Germany, have decreased significantly. A high percentage of the suspected cases was accepted as occupational disease, but persistent or permanent sequelae which conferred an entitlement to compensation were rare. Conclusion: There is scope to improve diagnosis and acceptance of tropical diseases as occupational diseases. The most important diseases reported were malaria, amoebiasis, and dengue fever. Comprehensive pre-travel advice and post-travel follow-ups by physicians trained in travel and occupational health medicine should be mandatory. Data indicate that there is a lack of knowledge on how to prevent infectious disease abroad.